Improving Readiness To Change In The Framework Of Crisis Management Project Of Algérietélécom Company - El Bey, Mohamed; Oura, Boubaker (جامعة الوادي- University of Eloued, 2016)
The face of the crisis is the title of this paper, but how? The response to the crisis it clear only through conducting exceptional Pollack unusual not in terms of qualitative and not quantitative management of these processes can be categorized in the door of project management, our words of this leads us to these processes directed to confront the crisis will involve regulatory changes, and its success will be primarily linked the extent of readiness of the organization to change and as the essence of crisis management will learn from previous crises and technology Communication is a tool of learning, we decided to study this element and diagnose the extent provided in the Etisalat Algeria, as well as its impact on the willingness to change, through the distribution of questionnaire to 322employee in the organization to verify the availability of use of communications technology, though it originally Communication Foundation and as well as provide a contribution to this element in their willingness to organizational change
The organizational learning approach
مقال
Keywords: crisis; readiness; change; organizationnal learning